Pendampingan Pembuatan Foto Produk untuk Konten bagi pelaku UMKM sebagai Upaya Promosi di Media Sosial - Sholeh, Muhammad; Rachmawati, Rr. Yuliana; Susetyo, Joko (Sevanam: Jurnal Pengabdian Masyarakat, 2022)
Community service activities carried out aim to provide insight to MSME entrepreneurs regarding making product photos that will be used on social media. Mentoring and training materials begin with materials that discuss the importance of using social media as promotional media and materials related to making product photos using simple equipment and packaging product photos with the Pixlr application. The use of the Pixlr application is so that the product photos that are used as content have more attractive value. Implementation of assistance is given to members of the Laras Manunggal MSME Sedayu District. The method of implementation begins with communicating with the board of the Laras Manunggal association, especially regarding the needs required by association members in the use of social media as a promotional media. The results of this communication were followed by a questionnaire to map the understanding of members related to social media. The results of this activity, among the participants, received material to make product photos which were carried out directly by practicing and evaluating the content made.